The nocturnal water cycle in an open‐canopy forest. Issue 17 (12th September 2013) - Berkelhammer, M.; Hu, J.; Bailey, A.; Noone, D. C.; Still, C. J.; Barnard, H.; Gochis, D.; Hsiao, G. S.; Rahn, T.; Turnipseed, A.
Abstract : [1] The movement of moisture into, out‐of, and within forest ecosystems is modulated by feedbacks that stem from processes which couple plants, soil, and the atmosphere. While an understanding of these processes has been gleaned from Eddy Covariance techniques, the reliability of the method suffers at night because of weak turbulence. During the summer of 2011, continuous profiles of the isotopic composition (i.e., δ 18 O and δ D) of water vapor and periodic measurements of soil, leaf, and precipitation pools were measured in an open‐canopy ponderosa pine forest in central Colorado to study within‐canopy nocturnal water cycling. The isotopic composition of the nocturnal water vapor varies significantly based on the relative contributions of the three major hydrological processes acting on the forest: dewfall, exchange of moisture between leaf waters and canopy vapor, and periodic mixing between the canopy and background air. Dewfall proved to be surprisingly common (∼30% of the nights) and detectable on both the surface and within the canopy through the isotopic measurements. While surface dew could be observed using leaf wetness and soil moisture sensors, dew in the foliage was only measurable through isotopic analysis of the vapor and often occurred even when no dew accumulated on the surface. Nocturnal moisture cycling plays a critical role in water availability in forest ecosystems through foliar absorption and transpiration, and assessing these dynamics, as done here, is necessary for fully characterizing the hydrological controls on terrestrial productivity. Key Points: Profiles of isotope ratio of H2O(v) yield new insight on nocturnal water cycling Dew is a critical source of bio‐available water and effects latent heat budget Deuterium‐excess of water vapor clearly tags canopy‐influenced moisture